The Effectiveness of Resocialization Carried out in the Interrogation Isolator from the Perspective of Convicts - Liukinevičienė, Laima; Mikalauskas, Donatas (Socialiniai tyrimai, 2018)
In recent years, in the Lithuanian science (Sakalauskas, 2007–2017; Uscila, 2012, 2015; Vaičiūnienė, 2017, etc.) and in the policy of custodial sentences, in terms of convicts’ social integration into society, in addition to the concept social rehabilitation, a wider term resocialization is used, as well as the differences between these concepts are perceived. Resocialization covers a wider context, and a number of assumptions determine the success of the resocialization of a convict in the imprisonment institutions. The implementation of resocialization requires not only the material and human resources of statutory institutions. In order to succeed in integrating a person into the society, a personalized access, the motivation of a convicted person himself/herself to change his/her behaviour have become important, the forces of enforcement authorities, the society (NGOs, volunteers, etc.), the continuing assistance to the person upon his/her release have been concentrated.Lithuania is taking the first steps in systematically managing the resocialization of imprisoned persons. Institutions of imprisonment face major challenges, because the successful rehabilitation of convicts requires the creation of appropriate conditions (close to life under release), to have the competent staff capable to identify the most serious motives of an offender and to individualize their needs to change, to have well-thought out programs of social adaptation, employment, etc., for whose implementation it is necessary to attract more people. Large public funds imply the need to assess whether the process of resocialization is effective.Summarizing the indicators which are currently used in imprisonment institutions and discussed by scholars as inadequate for assessing the effectiveness of resocialization (reduction of crime recidivism, the number of social rehabilitation programs and the number of convicts involved in them, the number of employees who acquired the competences necessary for the implementation of social rehabilitation process, etc.), the question is raised how to objectively evaluate the effectiveness of resocialization. Having found that the researchers (Schapland, Bottoms, Farrall, McNeill, Priede, Robinson, 2012) of the countries (Germany, England, the USA), which have best practices in the resocialization of convicts, advocate the use of subjective research in assessing the effectiveness of the resocialization process in imprisonment institutions, the survey was carried out in Šiauliai Interrogation Isolator to assess the effectiveness of the process of the social integration of convicts into society (the purpose of resocialization).For the survey carried out at the beginning of 2017, 397 men and women, who were imprisoned in Šiauliai Interrogation Isolator (hereinafter ŠII, the Isolator), were selected as the respondents. Answers to questions were provided by 279 respondents. The content of the quantitative research was expressed in five main thematic groups of questions: demographic, the evaluation of the activities of the Isolator social rehabilitation specialists, the change of services provided by an organization and their management, the efficiency of resocialization and social rehabilitation, and the influence of the environment on the convict’s resocialization.The structural composition of the 279 respondents according to gender is as follows: 95% of them indicated “a man”, 5% – “a woman”. According to the age, the persons of 18–40 years old (76%) prevailed in the research. Other age groups: 22% (41–55 years old) and more than 1% (56 years old and over). According to the education, a significant part of persons (47.7%) have the basic education, others have vocational (22.9%) and primary (21.5%) education. Out of them, 22 persons (7.9%) claimed that they have higher education (most of them were the arrested). Furthermore, 49.8 % of persons are imprisoned for the first time, 48.7% of respondents indicated, that they had served the custodial sentence before, the rest of the convicts did not mark this point in the questionnaire. In the research, the convicts were divided into: arrested persons, sentenced persons and sentenced persons to imprisonment.The results of the research showed that in this research we once again have actualized the strategic tasks of the last years of Lithuanian imprisonment institutions in the implementation of resocialization; we have indicated the strengths and weaknesses of an individual institution (in this case, in ŠII) in implementing the resocialization of the convicts; we have received the feedback from convicts about the quality and needs of the social rehabilitation measures implemented by Šiauliai Interrogation Isolator.Obviously, convicts see the benefits of resocialization for convicts in general and for themselves. In assessing critically the inadequate preparation of staff for the effective implementation of the planned social rehabilitation measures, the domestic and physical infrastructure of the interrogation isolator, the convicts are in favour of various employment opportunities (mostly work activity, physical education) and primarily organized in the open air. They appreciate the efforts of the heads of the social rehabilitation units devoted for their resocialization, however, they would like to get more of psychological help.Summing up the ideas provided by convicts, it is clear that in Šiauliai Interrogation Isolator, which until 2026, will be moved from the city centre of Šiauliai to the modern complex in Šiauliai district, the changes are necessary. The officials’ attitude towards the convicts has to change as well: the respondents who participated in the survey noted the unacceptable behaviour of the officials with the convicts. Household and physical conditions that respect human dignity are necessary. More help from psychologists and the examples of best practices are needed. The effectiveness of resocialization would be increased by meeting the demand for employment, and more employment measures in the open air. Developing democratic processes in the society should make it easier for convicts to take part in decision-making on their household conditions, employment programs, etc., to carry out a wider campaign of information on the possibility of convicts to learn, because currently only a small percentage of convicts use the adult learning centre established in the Isolator.
Keywords: social resocialization of convicts; social rehabilitation of convicts; imprisonment institution